2007
DOI: 10.1121/1.2715659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of speech production in upright and supine position

Abstract: Speech is usually produced in an upright sitting or standing posture. Measurements and judgments of speech may be made in conditions requiring a supine position, however. These conditions include MRI recordings, and oral procedures, such as, adjustments to dental appliances, medical and surgical procedures. It is of interest, therefore, to see whether gravity has strong or systematic effects on tongue behavior. In the present study, 13 subjects repeated several words, which contained extreme consonant and vowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
34
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 15 publications
7
34
0
3
Order By: Relevance
“…In the case of speech, intelligibility was preserved independently of the head's orientation. Stone et al (2007) observed similar differences in tongue movements during speech production in upright versus supine position. Simulations based on a realistic 3D biomechanical tongue model that employed the same motor commands for upright and supine position reproduced these differences (Buchaillard et al, 2009).…”
Section: Sequencing and Coarticulation In Limb Movementssupporting
confidence: 63%
“…In the case of speech, intelligibility was preserved independently of the head's orientation. Stone et al (2007) observed similar differences in tongue movements during speech production in upright versus supine position. Simulations based on a realistic 3D biomechanical tongue model that employed the same motor commands for upright and supine position reproduced these differences (Buchaillard et al, 2009).…”
Section: Sequencing and Coarticulation In Limb Movementssupporting
confidence: 63%
“…No consistent differences were found in formant frequencies or bandwidths between body positions or type of speech material. Stone et al (2007) and Tiede et al (2000) concluded from their data that the physiological effects of gravity on the acoustic properties of speech are negligible. Buchaillard et al (2009) concluded similarly from a biomechanical model of the tongue and oral cavity (OC).…”
mentioning
confidence: 99%
“…One of the most consistent observations is that the pharyngeal (nasopharyngeal and/or oropharyngeal) cavity is smaller in the supine as opposed to the upright position during speech, as determined from APh (Jan et al, 1994), computed tomography (CT; Sutthiprapaporn et al, 2008), MRI (Engwall, 2006;Kitamura et al, 2005;Traser et al, 2014), ultrasound (Stone et al, 2007;Wrench et al, 2011), x-ray microbeam (Tiede et al, 2000), and videofluoroscopy (Bae et al, 2014). This effect can be explained by gravity pulling the tongue root posteriorly when the subject is in the supine position, thereby reducing the size of the pharynx.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite huge technological advances enabling three-dimensional computer modeling of the structures examined, the MRI method still yields unsatisfactory results with regard to image accuracy and speed of sampling (speakers have to prolong a particular articulation, often for many seconds); it is also negatively influenced by the effect of gravity on articulation, because speakers have to lie down during testing (cf. Stone et al 2007). neither of the abovementioned methods - ultrasonography or magnetic resonance imaging - has been used in poland for articulation investigations.…”
Section: Introductionmentioning
confidence: 99%